Polyaniline films doped with ladder-type sulfonated polyphenylsilsesquioxane and unusual dependence of their electrical conductivity on temperature - Hong, Eun-Young; Lee, Suck-Hyun; Lee, Dong-Ki; Choi, Seung-Seok; Baek, Kyung-Youl; Hwang, Seung-Sang; Kwon, O-Pil (ROYAL SOC CHEMISTRY, 2012)
We report on conducting polyaniline (PANI) films doped with a thermally stable polymer dopant, linear ladder-type sulfonated polyphenylsilsesquioxane (S-PPSQ). The PANI/S-PPSQ films exhibited high-temperature stable electrical conductivity. With a heat treatment at 120 degrees C, the electrical conductivity of conventional PANI films doped with the molecular dopant camphorsulfuric acid (CSA) rapidly decreased to half of its initial value, while that of PANI/S-PPSQ films were relatively unaffected. Moreover, PANI/S-PPSQ films with high electrical conductivity exhibited unusual negative temperature coefficient of resistance (TCR) values above room temperature, in contrast to conventional PANI/CSA films that exhibited positive TCR values. By using a solution blend of PANI/S-PPSQ and PANI/CSA with negative and positive TCR values, respectively, we successfully demonstrated control of TCR behavior. Therefore, PANI/S-PPSQ materials are very promising for organic electronic applications.
Keywords: CAMPHORSULFONIC ACID; POLYMER